GAMBARAN BERAT LAHIR RENDAH BERDASARKAN KUALITAS PELAYANAN ANTENATAL CARE DI INDONESIA TAHUN 2012 (ANALISIS LANJUT SKDI 2012) - Izzah Dienillah Saragih, SKM., MKM (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2017)
ABSTRACT           LBW is one of indicator to describe public health status. In Indonesia, the prevalence of BBLR tends to stagnant and even increase by 6.7% in 2007 to 7.3% in 2012. Many factors affect the BBLR, one of which is the quality of Antenatal Care (ANC). This research is cross sectional study aimed to describe LBW based on ANC service quality by using data of SDKI 2012. Sampling process based on SDKI 2012 with study participant 13,413 respondent with descriptive analysis. Result of analysis found prevalence of LBW is 6,9%. 8619 (65.6%) respondents received good ANC quality with weight and abdominal examination, Fe pills suplementation as the highest coverage service standard. Based on the stratification of economic status, maternal employment status, and parity of LBW proportion in the group of mothers who received poorer ANC quality was higher in the group of poor economic status, working mother, and gave birth to 2-3 children. Mothers with these characteristics are expected to prepare better for subsequent pregnancies to prevent LBW occurrence and it is needed further investigation on factors related to ANC and LBW quality Keywords: LBW, Antenatal Care